2007
DOI: 10.1158/1535-7163.mct-06-0643
|View full text |Cite
|
Sign up to set email alerts
|

Selenium sensitizes MCF-7 breast cancer cells to doxorubicin-induced apoptosis through modulation of phospho-Akt and its downstream substrates

Abstract: Doxorubicin is an effective drug against breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 23 publications
4
86
0
Order By: Relevance
“…Synergistic tumor growth inhibition and reduced toxicity were shown by combination of organic selenium with the topoisomerase I poison irinotecan or doxorubicin in tumorbearing mice inoculated with cancer cells sensitive and resistant to irinotecan (19,20). Similar reports of synergy between selenium and chemotherapeutic drugs were recently reported in breast cancer (20).…”
Section: Introductionsupporting
confidence: 70%
“…Synergistic tumor growth inhibition and reduced toxicity were shown by combination of organic selenium with the topoisomerase I poison irinotecan or doxorubicin in tumorbearing mice inoculated with cancer cells sensitive and resistant to irinotecan (19,20). Similar reports of synergy between selenium and chemotherapeutic drugs were recently reported in breast cancer (20).…”
Section: Introductionsupporting
confidence: 70%
“…Although flow cytometry analysis of Annexin V and PI double staining is a wellaccepted assay to determine apoptotic cell death, this method is not suitable for cells treated with DOX as it emits a very strong and broad-band fluorescence that interferes with the assay (16). Considering the afore-mentioned problem, we used trypan blue staining instead to quantify cell death caused by ASA, DOX, or the combination.…”
Section: Asa Promotes Dox-induced Cell Death In Vitromentioning
confidence: 99%
“…Apoptosis has been described as one of the more important mechanisms for the anticancer action of selenium-based compounds. [35][36][37] Although Valdiglesias et al 38 reported that the induction of apoptosis by Seleniumbased compounds may be related to changes in the cell cycle, Suchocki et al 20 found that free selol did not overset the cell cycle in human leukemia cells.…”
Section: Discussionmentioning
confidence: 99%